Metal–Organic Frameworks Based Electrocatalysts for the Oxygen Reduction Reaction - Lu, Xue Feng; Xia, Bao Yu; Zang, Shuang‐Quan; Lou, Xiong Wen (David) (Angewandte Chemie International Edition, 2020)
In view of the clean and sustainable energy, metal–organic frameworks (MOFs) based materials, including pristine MOFs, MOF composites, and their derivatives are emerging as unique electrocatalysts for oxygen reduction reaction (ORR). Thanks to their tunable compositions and diverse structures, efficient MOF‐based materials provide new opportunities to accelerate the sluggish ORR at the cathode in fuel cells and metal–air batteries. This Minireview first provides some introduction of ORR and MOFs, followed by the classification of MOF‐based electrocatalysts towards ORR. Recent breakthroughs in engineering MOF‐based ORR electrocatalysts are highlighted with an emphasis on synthesis strategy, component, morphology, structure, electrocatalytic performance, and reaction mechanism. Finally, some current challenges and future perspectives for MOF‐based ORR electrocatalysts are also discussed. Despite the rapid developments in the past decade, many great challenges remain for the practical use of metal–organic frameworks (MOFs) based electrocatalysts. This Minireview summaries some major recent research efforts and advances on MOF‐based electrocatalysts for the oxygen reduction reaction. Some promising directions and strategies are also discussed.